IMPLEMENTASI PERMENPAN DAN REFORMASI BIROKRASI NOMOR 20 TAHUN 2010 TENTANG ROAD MAP REFORMASI BIROKRASI DI SETDA KAB. GORONTALO - Tome, Abdul Hamid; Paramata, Sri Hantuti (AKADEMIKA, 2013)
Government bureaucracy has negative face in front of society nowadays due to its slow performance and its huge corruption. Therefore the president tried to solve this problems issued the Presidential Decree No .81 of 2010. This effort was then followed up by the Minister for Administrative Reforms PAN through ministerial regulations numbered 20 in 2010 about Bureaucratic Reform Road Map. The purpose of this paper is first, to undertake judicial review of the implementation of Reforms No. Permenpan .20 In 2010. Second, to determine the factors that influence the success rate and inhibiting the implementation of No. Permenpan. 20 of 2010. Third, to determine the impact of the implementation of No. Permenpan. 20 In 2010 in the Secretariat of Gorontalo. This research used a normative legal research method through conceptual approach and legislation. The data was collected by literature review to obtain a theoretical foundation from the experts and by interview to gain information about legal provisions contained in the legislation. This data was then analyzed using descriptive methods. The results showed that first, local governments have implemented Permenpan Gorontalo and No. Bureaucratic Reform. 20 in 2010. Second, there are three inter-related factors in the implementation of the bureaucratic reform which are leadership commitment, involvement of all civil servants, and compliance in carrying out the road map. Third, the implementation of bureaucratic reform in the District. Gorontalo showed the strong desire to reform the bureaucracy, the establishment of good governance and corruption-free, improving the quality of public services and strengthening government performance akuntabulitas